Fundamentals of an African-Centred Syllabus in Higher Education in the Post-Colonial Era: The Tehuti Perspective - Mthembu, Ntokozo (International Journal of Criminology and Sociology, 2022)
Socio-political change in South Africa, also known as Azania,1 brought about the high hopes and opportunities, especially among the black African majority, in this instance, the recognition and revitalisation of their knowledge systems, in particular, in the learning sphere. The name, Azania becomes more relevant in this discussion, as it divulges the basis of indigenous African knowledge and related methodology systems, specifically on issues that encompass knowledge creation, categorisation and classification of events and circumstances. Nevertheless, the review of literature on the significance of aspects of African knowledge creation such as Tehuti perspective is revealed in this instance. This manuscript posits that diverse paradigms often influence the research approach in a particular milieu. It also suggests that the Tehuti perspective will facilitate the eradication of stereotyping imposed by the narrow cultural perspective in the social sphere including education, especially when it comes to research approach. It concludes by highlighting the need for consideration of diverse knowledge value systems, in particular, when dealing with narratives as indicative of a particular milieu rather than a prescriptive.